Keputusan Pembelian Konsumen Ditinjau dari Word of Mouth dan Lokasi pada Konveksi Sablon Majapahit di Mojokerto - Kartika Laila Dewi; M. Syamsul Hidayat; Kasnowo Kasnowo (Pajak dan Manajemen Keuangan, 2025)
This study aims to analyze the influence of word of mouth and location on consumer purchasing decisions at Konveksi Sablon Majapahit in Mojokerto. The research employs a quantitative approach with data collected through online questionnaires. The sample was selected using purposive sampling based on specific criteria. Data were analyzed using multiple linear regression with the assistance of SPSS version 27. The results indicate that both word of mouth and location have a significant partial and simultaneous effect on purchasing decisions. Location is proven to be a more dominant factor than word of mouth. The coefficient of determination (R²) of 0.785 indicates that 78.5% of the variation in purchasing decisions can be explained by these two variables. This research is expected to serve as a practical reference for garment business owners in formulating effective marketing strategies.